the description of the use social media on the risk of narcissistic behavior on students at the riau islamic university - annisa dwi kartika, annisa dwi kartika (Afiasi : Jurnal Kesehatan Masyarakat, 2020)
The most frequent activity to attract the attention of Instagram users is to do selfies for teenagers or adults. This is related to narcissistic behavior that is where someone loves themselves excessively, the more often they upload photos or videos, added with lots positive comments, it will increase the individual's desire. The objective of this research is to determine the description of Instagram social media users on the risk of narcissistic behavior in students. The study was conducted at Riau Islamic University Pekanbaru. This research used descriptive research design with simple random sampling technique, the sample in this study were 100 respondents. Analysis used univariate analysis. The results showed that 46 (46%) were at risk and that were not at risk as much as 54 (54%), felt themselves the greatest were 18 (31.1%), were filled with fantasies, found 27 (58.7%), had confidence that they were special obtained 24 (52.2%), excess need to be admired was 35 (76.1%), big name was obtained 32 (39.6%), interpersonal exploitation was obtained 24 (52.2%), lack of empathy was obtained 37 (80.4%), envy of others was 26 (56.5%), showed arrogant attitudes obtained 33 (71.7%). The results of the analysis are expected to the development of nursing science to be able to provide information such as counseling to students who are narcissistic. Keywords: Instagram, Narcissistic, Behavior